1981
DOI: 10.1093/nar/9.4.879
|View full text |Cite
|
Sign up to set email alerts
|

The use of synthetic oligonucleotides as hybridization probes. II. Hybridization of oligonucleotides of mixed sequence to rabbit β-globin DNA

Abstract: Two oligonucleotides 14-bases long were synthesized, one complementary to rabbit beta-globin DNA (R beta G14A) and the other with the same sequence except for a single base change (T for C) (R beta G14B). Hybridization conditions were established such that R beta G14A would hybridize to globin DNA while R beta G14B would not. We also synthesized a mixture of 13-base long oligonucleotides (R beta G13Mix), representing eight of the possible coding sequences for amino acids 15-19 of rabbit beta-globin. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
183
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(184 citation statements)
references
References 20 publications
(14 reference statements)
1
183
0
Order By: Relevance
“…Transformation of E. eoti MC 1061 or HB101 was carried out according to Bolivar & Backman (1979) using RbCI. Colony hybridizations using synthetic oligodeoxynucleotides were performed as in Wallace et al (1981 a).…”
Section: Methodsmentioning
confidence: 99%
“…Transformation of E. eoti MC 1061 or HB101 was carried out according to Bolivar & Backman (1979) using RbCI. Colony hybridizations using synthetic oligodeoxynucleotides were performed as in Wallace et al (1981 a).…”
Section: Methodsmentioning
confidence: 99%
“…The foundation for clinical use of this strategy was the finding in 1981 (Wallace et al, 1981) that hybridization conditions could be found that allowed a 14-base-pair oligonucleotide to bind when perfectly matched and not bind when a single base pair mismatch occurred in the duplex. This system has been used and developed extensively up to the present.…”
Section: Mutation Detection Methods Where the Mutation Position Is Knmentioning
confidence: 99%
“…2), following the suppliers' recommendations (Biihringer Mannheim ; BRL; Pharmacia). The resulting fragments were separated on a 1 % (w/v) agarose gel, blotted onto nylon filters (Pall) and hybridized to the [~~~PIATP-end-labelled oligonucleotide probes (Wallace et al, 1979(Wallace et al, , 1981Conner et al, 1983).…”
Section: U B Gobel a G E I S E R A N D E J S T A N B R I Dmentioning
confidence: 99%